2013
DOI: 10.1152/ajpendo.00016.2013
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial microparticles increase in mitral valve disease and impair mitral valve endothelial function

Abstract: (HMVECs) were treated with EMPs. The phosphorylation of Akt and endothelial nitric oxide synthase (eNOS), the association of eNOS and heat shock protein 90 (HSP90), and the generation of nitric oxide (NO) and superoxide anion (O2˙Ϫ) were measured. EMPs were increased significantly in patients with mitral valve disease compared with those in healthy subjects. EMPs were negatively correlated with mitral valve area in patients with isolated mitral stenosis. EMPs were significantly higher in the group with severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 43 publications
1
47
0
Order By: Relevance
“…At the end of the MP incubation period, the supernatant was used to determine NO generation using an NO detection kit (Nanjing Jiancheng Bioengineering Institute, Nanjing, China). Aortic samples were dried and weighed, and NO generation was reported as nanomoles per milligram protein [23]. …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…At the end of the MP incubation period, the supernatant was used to determine NO generation using an NO detection kit (Nanjing Jiancheng Bioengineering Institute, Nanjing, China). Aortic samples were dried and weighed, and NO generation was reported as nanomoles per milligram protein [23]. …”
Section: Methodsmentioning
confidence: 99%
“…After washing, the aortic proteins were harvested and immunoblots performed as previously described [23]. Antibodies to Akt (Cell Signaling Technology, Beverly, Mass., USA), phosphorylated Akt (Cell Signaling Technology), endothelial NO synthase (eNOS; Santa Cruz Biotechnology, Santa Cruz, Calif., USA), eNOS phosphorylated at Ser 1177 (Cell Signaling Technology) and β-actin (Cell Signaling Technology) were used for Western blot analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In such patients, the higher number of circulating MPs may contribute to the progression of atherosclerotic disease and enhanced cardiovascular risk [16]. In patients with atrial fibrillation, the secretion of endothelial MPs could play a role in maintaining the prothrombotic and inflammatory process [17]. Interestingly, it has been shown that the level of MPs declines after the restoration of sinus rhythm [18].…”
mentioning
confidence: 99%